Myocardial regeneration strategy using Wharton’s jelly mesenchymal stem cells as an off-the-shelf ‘unlimited’ therapeutic agent: results from the Acute Myocardial Infarction First-in-Man Study - Musialek, Piotr; Mazurek, Adam; Jarocha, Danuta; Tekieli, Lukasz; Szot, Wojciech; Kostkiewicz, Magdalena; Banys, R. Pawel; Urbanczyk, Malgorzata; Kadzielski, Andrzej; Trystula, Mariusz; Kijowski, Jacek; Zmudka, Krzysztof; et al. (Postępy w kardiologii interwencyjnej, 2015)
In large-animal acute myocardial infarction (AMI) models, Wharton's jelly (umbilical cord matrix) mesenchymal stem cells (WJMSCs) effectively promote angiogenesis and drive functional myocardial regeneration. Human data are lacking. To evaluate the feasibility and safety of a novel myocardial regeneration strategy using human WJMSCs as a unique, allogenic but immuno-privileged, off-the-shelf cellular therapeutic agent. The inclusion criterion was first, large (LVEF ≤ 45%, CK-MB > 100 U/l) AMI with successful infarct-related artery primary percutaneous coronary intervention reperfusion (TIMI ≥ 2). Ten consecutive patients (age 32-65 years, peak hs-troponin T 17.3 ±9.1 ng/ml and peak CK-MB 533 ±89 U/l, sustained echo LVEF reduction to 37.6 ±2.6%, cMRI LVEF 40.3 ±2.7% and infarct size 20.1 ±2.8%) were enrolled. 30 × 10(6) WJMSCs were administered (LAD/Cx/RCA in 6/3/1) per protocol at ≈ 5-7 days using a cell delivery-dedicated, coronary-non-occlusive method. No clinical symptoms or ECG signs of myocardial ischemia occurred. There was no epicardial flow or myocardial perfusion impairment (TIMI-3 in all; cTFC 45 ±8 vs. 44 ±9, p = 0.51), and no patient showed hs-troponin T elevation (0.92 ±0.29 ≤ 24 h before vs. 0.89 ±0.28 ≤ 24 h after; decrease, p = 0.04). One subject experienced, 2 days after cell transfer, a transient temperature rise (38.9°C); this was reactive to paracetamol with no sequel. No other adverse events and no significant arrhythmias (ECG Holter) occurred. Up to 12 months there was one new, non-index territory lethal AMI but no adverse events that might be attributable to WJMSC treatment. This study demonstrated the feasibility and procedural safety of WJMSC use as off-the-shelf cellular therapy in human AMI and suggested further clinical safety of WJMSC cardiac transfer, providing a basis for randomized placebo-controlled endpoint-powered evaluation.